Jaringan Syaraf Tiruan Untuk Klasifikasi Status Gizi Balita Jenis Kelamin Laki-laki Dengan Metode Backpropagation - Fathina, Hasna (2015)
Rate nutritional status of children is one of the most important things to know infant health. , Research neural networks to classification of nutritional status of children, aiming to facilitate the assessment of medical personnel in providing the nutritional status of children. System design method used is the waterfall method that uses a systematic approach and sequence ranging from the level of defining the system requirements to maintenance. While the methods used to classification of nutritional status of children is backpropagation method. Backpropagation method is one that is frequently used algorithms in solving complex problems. this allows for network algorithm trained using supervised learning methods. Based on the results of the test system, The results of this research is a neural network application which facilitates an expert e( doctor , midwife or nutritionist ) in its assessment of nutritional status of children under five male gender .